The Island of Love/The Island of Conflict: Hospitality and Hostility of Turkish Cypriot Identity and Citizenship in North Cyprus - Ilter, Tugrul (Routledge Journals, Taylor & Francis Ltd, 2015)
This paper deals with the hospitality and hostility of Turkish Cypriot identity in North Cyprus in its various configurations today. It contends that we become who we are by extending hospitality to different and differing representations of who we are like a name or a land, all the while being unable to reduce this differential relationship to a self-identical ipseity. This differential relationship is the origin of identity and not a singularly self-sufficient subjectivity inherited from a past history and culture. Using the alibi of an inheritance cannot hide our complicity in the production of that history and culture anew in the present. This shift in perspective opens Turkish Cypriot identity to its future becoming, hopefully to a future beyond ethnocentrism, towards a form of solidarity different from the border politics of a paternal hospitality like that of nation states.
Keywords: Hospitality; North Cyprus; Ethnocentrism; Identity; Nationalism; Intercultural Communication